Islamic Values and Education in Sufiya Ahmed’s Secrets of the Henna Girl - Annisa Nur Chaliza; Hasnul Insani Djohar (Muslim English Literature, 2022)
This research examines how Sufiya Ahmed’s Secrets of Henna Girl challenges patriarchal practices by depicting the female character as struggling to fight for their rights through Islamic values and education. By using qualitative methods and close textual analysis, this research examines how the novel opposes to patriarchal culture and the misconception of Islam as a religion that supports discrimination against women. Indeed, the novel uses literary devices to portray patriarchal culture with the following aspects: the female characters experience patriarchal abuse by depicting men as Tiger King represents powerful men. Secondly, the female characters deal with patriarchal system by depicting women as witches representing powerful women. Thirdly, women experienced patriarchal abuse are depicted through the metaphor of glass vases and sacrificed lambs. Fourthly, the characters are depicted as a drama queen if they pursue their educations and careers. Although this novel is seemingly depicted women as the victims of patriarchal system, they are able to resist this system by using Islamic tenets and values, especially the Quran and hadiths. Furthermore, it is found that even though the female characters receive so many patriarchal practices, the novel can depict them as resisting patriarchy through education and Islamic values. Thus, the novel uses Qur’an, hadith, and Islamic teachings as a way to resist the misconception of Islam as a religion that supports discrimination against women.